CONFLICT AND CONVERGENCE BETWEEN CRIMINAL LAW AND RELIGIOUS LAW (A CRIMINOLOGICAL PERSPECTIVE) - Gunawan Widjaja; Adrian Bima Putra (Adisam Publisher, 2025)
This article discusses the conflict and convergence between criminal law and religious law from a criminological perspective. This conflict often occurs due to differences in principles and norms between the two legal systems, which can include differences in sentencing, views on justice, and the protection of human rights. On the other hand, however, convergence can be found when the ethical and moral principles espoused in religious law support the objectives of secular criminal law, such as in crime prevention and the protection of society. Through criminological analysis, this article explores how these conflicts and convergences affect the implementation of the law, public perceptions of justice, and the formulation of more inclusive and effective criminal policies. The article concludes that by carefully considering the differences and similarities between the two legal systems, areas in need of reform or adjustment can be identified to improve the effectiveness of the justice system and promote social justice.